Making more of potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A staple crop which can yield four times as many calories per hectare as rice, or five times as many as wheat, is enjoying a consumer success that has encouraged many farmers to increase production. The Irish potato (Solanum tuberosum) is becoming...